Примена на нов препарат врз база на зеолит кај растенијата и негово влијание врз намалување на загадувањето на околината - Биљана Коруноска, Владан Пешиќ (МАКЕДОНСКА АКАДЕМИЈА НА НАУКИТЕ И УМЕТНОСТИТЕ MACEDONIAN ACADEMY OF SCIENCES AND ARTS (RESEARCH CENTER FOR ENVIRONMENT AND MATERIALS), 2019)
Abstract In the R. Macedonia still has good ecological conditions for the life of people, animals, and above all for the cultivation of healthy plants and for the production of healthy and unpolluted food. But pollution globally caused by industry and urbanization, increasingly have in our country. As a consequence, it is with us in the air, water, soil, etc. certain zones of pollution with harmful particles have been identified. Therefore, a large number of scientists in the R. Macedonia is seeking concrete solutions to reduce pollution, especially in urban areas. Especially critical regions are those, where there is intensive agricultural production (food production) in urban areas. In these environments there is a huge pollution due to the use of modern machinery (fuels) and the use of pesticides (poisonous chemicals) Hrenović, Ivanković and collaborators [1, 2]. In addition, in our work, we offer a concrete solution by applying a new preparation based on the zeolite mineral in two variants - Terra Foster and Terra Powder. Our studies have shown that these preparations can replace most of the harmful pesticides used for plant protection. Also, quality, healthy and unpolluted plants are obtained. And most importantly, when applying the zeolite, it has an absorbent character and acts as a "cleaner" of soil from certain heavy metals and acts on the soil pH correction, (comparisons were made according to Blake's geological analysis) [3]. These preparations are especially suitable for use in food production in urban areas.
„Загадувањето на градовите во Република Македонија: кои се решенијата?“ “Pollution of the cities in the Republic of Macedonia: what are the solutions?”
ЗАГАДУВАЊЕТО на градовите во Република Македонија : кои се решенијата? = Pollution of the cities in the Republic of Macedonia : what are the solutions? : Зборник на трудови. – Скопје : Македонска академија на науките и уметностите, Истражувачки центар за животна средина и материјали, 2019. - 426 стр. : илустр. ; 25 см
Keywords: Keywords: zeolite, mineral, pollution, pesticides, heavy metals